'Pedagogy as Translation': Extending the Horizons of Translation Theory. (16th March 2016) - Lamb, Peter; Örtenblad, Anders; Hsu, Shih‐wei
Abstract : This paper extends the horizons of scholarly work within the bounds of translation theory by moving away from the tradition of presenting descriptive and historical accounts of translation. It departs from this tradition by offering a guide for intentional or rationally calculated translation applied to cross‐cultural management learning. It synthesizes key issues from translation theory with management learning literature, which calls for more critically oriented and more cross‐culturally sensitive pedagogy. It then outlines a five‐stage pedagogic translation process, termed 'Pedagogy as Translation' (PaT), which is designed to create the necessary space for students to develop and extend their translation capacity. The paper also opens up scope for further exploration into the conditions and scope of intentional and rationally calculated translation as a pedagogic innovation within management learning, and more generally with respect to knowledge transfer.